2020
DOI: 10.3390/ijms21062066
|View full text |Cite
|
Sign up to set email alerts
|

Resvega Alleviates Hydroquinone-Induced Oxidative Stress in ARPE-19 Cells

Abstract: Retinal pigment epithelial (RPE) cells maintain homeostasis at the retina and they are under continuous oxidative stress. Cigarette smoke is a prominent environmental risk factor for age-related macular degeneration (AMD), which further increases the oxidant load in retinal tissues. In this study, we measured oxidative stress and inflammatory markers upon cigarette smoke-derived hydroquinone exposure on human ARPE-19 cells. In addition, we studied the effects of commercial Resvega product on hydroquinone-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 54 publications
3
29
0
Order By: Relevance
“…It is in line with our previous study where we saw that 25 μM Resvega alone did not compromise cell viability [ 30 ]. We have previously shown that Resvega can improve cell viability determined by both MTT and LDH assays during hydroquinone-induced oxidative stress or MG-132 exposure on ARPE-19 cells [ 29 , 30 ]. In the present study, Resvega preserved the integrity of cell membranes with disrupted protein clearance but had no effect on the cellular metabolic activity measured using the MTT assay.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is in line with our previous study where we saw that 25 μM Resvega alone did not compromise cell viability [ 30 ]. We have previously shown that Resvega can improve cell viability determined by both MTT and LDH assays during hydroquinone-induced oxidative stress or MG-132 exposure on ARPE-19 cells [ 29 , 30 ]. In the present study, Resvega preserved the integrity of cell membranes with disrupted protein clearance but had no effect on the cellular metabolic activity measured using the MTT assay.…”
Section: Discussionmentioning
confidence: 99%
“…The level of IL-6 was reduced by MG-132, a well-known NF-κB inhibitor, with bafilomycin [ 40 ]. We have previously shown that hydroquinone-mediated NF-κB inhibition resulted in diminished IL-6 levels, where Resvega returned to the control level independently of NF-κB activation [ 29 ]. In the present study, 10 μM Resvega had no additional effect on the IL-6 release upon MG-132 and BafA treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a number of lifestyle factors, including smoking [ 21 ], improper dietary intake [ 22 , 23 ], obesity [ 24 ], and lack of exercise [ 25 ], are associated with a higher prevalence of AMD. Cigarette smoke can cause accumulation of cadmium (Cd) [ 26 ] and further increase the oxidant load in retinal tissues [ 27 ]. Dietary zinc deficiency can sensitize RPE cells to oxidative damage [ 28 ].…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%